Familismo amorale e marginalità storica ovvero perché non c’è niente da fare a Montegrano (1967) - Alessandro Pizzorno (Quaderni di Sociologia, 2019)
Banfield’s work does not follow the research model it had previously proposed for the following reasons: 1) the behavior of the people of Montegrano is not reducible to che simple maximization of the material and immediate advantage of the family nucleus.2) the people of Montegrano are not making the least effort to amelionrate their conditions because nothing which they could do would do any better to them. Banfield moreover is conscious of this. 3) The amoral familism does not explain why in Montegrano people live in such conditions that, being in Montegrano, nothing could be done to change things.4) Banfield fails to identify the causes of the situation of Montegrano because in his analysis he assumes Montegrano ad an isolated object. 5) to understand Montegrano it is rather necessary to study the phenomenon of historical marginality, a situation typical of communities like Montegrano.